2024
DOI: 10.1159/000538282
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon, induced by adenovirus or adenoviral vector infection, regulates the cytokine response to LPS in a macrophage type-specific manner

Mareike D. Maler,
Sophie Zwick,
Carsten Kallfass
et al.

Abstract: In mice, adenovirus (Ad)-elicited IFN-ab mediates the overproduction of LPS stimulated cytokines such as TNFa and IL-6. We found that Ad infection also mediates the overproduction of IFN-ab itself and enables its production in splenic marginal zone macrophages, which don’t produce IFN-ab in response to LPS alone. We show the importance of the scavenger receptor MARCO for Ad uptake and cytokine overproduction in vivo, and the differential contribution of infection and rIFN-b to LPS-induced cytokine response in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
(177 reference statements)
1
0
0
Order By: Relevance
“…We found that exogenous IFNβ enhanced AM production of TNF and IL-6 in response to low-dose LPS. This is supported by a recent study demonstrating that adenoviral-induced IFNβ enhances AM and AM-like responses to LPS 59 . IFNβ did not appear to directly enhance PRR or adaptor expression and it is still unknown what mediates this enhanced response.…”
Section: Discussionsupporting
confidence: 68%
“…We found that exogenous IFNβ enhanced AM production of TNF and IL-6 in response to low-dose LPS. This is supported by a recent study demonstrating that adenoviral-induced IFNβ enhances AM and AM-like responses to LPS 59 . IFNβ did not appear to directly enhance PRR or adaptor expression and it is still unknown what mediates this enhanced response.…”
Section: Discussionsupporting
confidence: 68%